Direct and indirect effects of adverse and protective childhood experiences on symptom improvement in psychotherapy [results] - Kindermann, David; Dönnhoff, Ivo; Orth, Maximilian; Friederich, Hans-Christoph; Nikendei, Christoph (Universität, 2023)
Analysis of the psychotherapy data from the HIP (Heidelberger Institute for Psychotherapy). We checked whether the speed of patients' symptom improvement depended on their childhood experiences. We used the structural integration of personality as mediating factors. (2022-12-05)
Gesehen am 19.03.2024
Keywords: Forschungsdaten; Datenbank